1987
DOI: 10.1246/bcsj.60.3619
|View full text |Cite
|
Sign up to set email alerts
|

Excimer Formation and Induced-Fit Type of Complexation of β-Cyclodextrin Capped by Two Naphthyl Moieties

Abstract: Host–guest complexation of β-Cyclodextrin bearing two naphthyl moieties (1) has been studied by circular dichroism and fluorescence spectroscopic methods. The circular dichroism spectrum exhibits a positive band around 225 nm while the fluorescence spectrum exhibits a predominant monomer peak with a shoulder of excimer emission. These data suggest that 1 can take two forms, one of two naphthyl moieties being included in the cavity of the predominant form (A) while both naphthyl moieties being located outside o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The fluorescent CD exhibited strong emission in the self-inclusion state due to the hydrophobic environment of the CD cavity and exclusion of the fluorophore from the cavity to bulk aqueous media weakened its fluorescence intensity. They synthesized “turn-off” fluorescent chemical sensors of CD derivatives carrying fluorophore compounds such as dansyl [30-35], dimethylaminobenzoyl [36-38], naphthyl [39-41], pyrene [42] and anthracene [43,44] moieties. Moreover, a new type of “turn-on” fluorescent chemical sensors, in which fluorescence intensity was increased by formation of host-guest complexes, was also reported (Figure 2b).…”
Section: Chemical Sensors Using Chromophore Appended Cdsmentioning
confidence: 99%
“…The fluorescent CD exhibited strong emission in the self-inclusion state due to the hydrophobic environment of the CD cavity and exclusion of the fluorophore from the cavity to bulk aqueous media weakened its fluorescence intensity. They synthesized “turn-off” fluorescent chemical sensors of CD derivatives carrying fluorophore compounds such as dansyl [30-35], dimethylaminobenzoyl [36-38], naphthyl [39-41], pyrene [42] and anthracene [43,44] moieties. Moreover, a new type of “turn-on” fluorescent chemical sensors, in which fluorescence intensity was increased by formation of host-guest complexes, was also reported (Figure 2b).…”
Section: Chemical Sensors Using Chromophore Appended Cdsmentioning
confidence: 99%
“…2). Moriwaki et al (1987) reported that 6A,6D-bis(2-naphthylacetyl)-P-CD exhibits similar induced-fit type of complexation. A smaller extent of enhancement in the excimer emission was observed for 5, so there exists some difficulty for the two naphthyl rings of 5 to form the excimer both in and outside the cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Camphor, fenchone, menthol, geraniol, nerol, cyclohexanol, and cyclooctanol compete with azobenzene residue to a lesser extent than l-borneol, 1adamantanol, or 1-adamantanecarboxylic acid [53,54]. Ueno et al [55,56] showed that β-cyclodextrin arched with azobenzene-4,4'dicarbonyl-and azobenzene-4,4'-disulfonyl-residues ( Figure 19) have enlarged hydrophobic cavity, particularly in the case of the cis isomers. The respective AD and AE regioisomers of azobenzene-4,4'-disulfonyl derivative of γ-cyclodextrin were obtained by Hamada et al [57] (Figure 19).…”
Section: Figure 15mentioning
confidence: 99%